Protegiéndose del río Rímac: Los tajamares o muros de contención de Lima durante la colonia - Rivasplata Varillas, Paula Ermila (2015)
One of the frecuent problems of colonial Lima was the violence of Rimac river when makes bigger its flow during the Southern Hemisphere summer. The summer rain and the ice melt of the Central Andes flows down carryng much water, eroding its banks and take away what it finds in its way. The limeños maintained a prolonged struggle against the Rímac river by means of the tajamares. They were so afraid of the river that every year the walls to contain it had to be reenforced, financed by special sale taxes on the meat, among other products. According to father Bernabé Cobo of the Company of Jesus, paying the tax on meat was like throwing it down to the river. The building of these water defenses was in charge of lay and religious experts employing Indian manpower. The tajamares ran through the San Cristóbal hill down beyond the Santo Domingo monastery. All these efforts of rebuilding during the sixteenth and seventeenth centuries produced by the beginning of the eighteenth graceful defenses as well as attractive sidewalks by the river side.